2013
DOI: 10.1007/s10433-013-0273-9
|View full text |Cite
|
Sign up to set email alerts
|

Religious activity, life expectancy, and disability-free life expectancy in Taiwan

Abstract: Research has implicated religious activity as a health determinant, but questions remain, including whether associations persist in places where Judeo-Christian religions are not the majority; whether public versus private religious expressions have equivalent impacts, and the precise advantage expressed as years of life. This article addresses these issues in Taiwan. 3,739 Taiwanese aged 53? were surveyed in 1999, 2003, and 2007. Mortality and disability were recorded. Religious activities in public and priva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 44 publications
0
4
0
1
Order By: Relevance
“…Although there has been research investigating the association between religiosity and health across a wide range of countries (Zimmer et al, 2018 ), including Europe (Ahrenfeldt et al, 2017 ; Nicholson et al, 2009 , 2010 ), our study is the first to consider mortality and health simultaneously in healthy life expectancy across multiple countries. Previous studies on this topic were carried out only in single countries, Taiwan (Hidajat et al, 2013 ; Zimmer et al, 2020 ) and Sweden (Schön et al, 2011 ). At an individual level, our finding of a stronger positive relationship between health and religiosity for attendance than any other dimension confirmed results of a study that found significant positive associations between attendance and health in Finland, Greece and Ireland, and a negative relationship between prayer and health in Estonia (Nicholson et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although there has been research investigating the association between religiosity and health across a wide range of countries (Zimmer et al, 2018 ), including Europe (Ahrenfeldt et al, 2017 ; Nicholson et al, 2009 , 2010 ), our study is the first to consider mortality and health simultaneously in healthy life expectancy across multiple countries. Previous studies on this topic were carried out only in single countries, Taiwan (Hidajat et al, 2013 ; Zimmer et al, 2020 ) and Sweden (Schön et al, 2011 ). At an individual level, our finding of a stronger positive relationship between health and religiosity for attendance than any other dimension confirmed results of a study that found significant positive associations between attendance and health in Finland, Greece and Ireland, and a negative relationship between prayer and health in Estonia (Nicholson et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps, the nervous system represents the locus of a mechanism by which religious faith or beliefs promote well-being. Among Taiwanese older adults, higher levels of religious activity mean more expected years lived and more expected years lived without an activities-of-daily-living (ADL) disability [ 32 ]. Religiosity was found to be related to mental and physical health in the US; it predicted positive affects (affection, joy, love, happiness, contentment, caring, pride, and fondness), fewer mental health ailments, and lower levels of cognitive intrusions [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Zeng, Gu, and George (2011) found little connection between religious participation and mortality among Chinese elders. Earlier Taiwan-based studies by Yeager et al (2006) and Hidajat, Zimmer, Saito, and Lin (2013) showed associations in Taiwan differed across health outcomes. Liu, Schieman, and Jang (2011) concluded that religious beliefs and supernatural activities in Taiwan associated with more distress, while prayer was associated with less.…”
Section: Discussionmentioning
confidence: 96%